Complexity, prototypicality, familiarity, and the perception of musical quality - North, Adrian; Hargreaves, David (University of Prince Edward Island * Department of Psychology, 2001)
Evaluative responses to music have been neglected in relation to affective responses, and the present research investigated the relationships between ratings of musical quality, and those of liking, complexity, prototypicality, and familiarity. Fifty subjects rated 24 musical excerpts on 11-point scales based on these five variables. In accordance with previous research, a positive correlation was maintained between ratings of liking and quality. Partial correlation and multiple regression analyses demonstrated that complexity explained more of the variance in quality ratings than either prototypicality or familiarity.